Development and validation of HPLC method for quantitative analysis of triamcinolone in biodegradable microparticles - Silva, A. A. [UNESP]; Formariz, T. P. [UNESP]; Scarpa, M. V. [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (My University, 2006)
A simple, rapid, selective and specific high performance liquid chromatographic (HPLC) method for quantitative analysis of the triamcinolone in polylactide-co-glycolide acid (PLGA) microparticles was developed. The chromatographic parameters were reversed-phase C18 column, 250mm x 4.6mm, with particle size 5 μm. The column oven was thermostated at 35°C ± 2°C. The mobile phase was methanol/water 45:55 (v/v) and elution was isocratic at a flow-rate of 1 mL.mL-1. The determinations were performed using a UV-Vis detector at 239 nm. The injected sample volume was 10 μL. The standard curve was linear (r2 > 0.999) in the concentration range 100-2500 ng.mL-1. The method showed adequate precision, with a relative standard deviation (RSD) was smaller than 3%. The accuracy was analyzed by adding a standard drug and good recovery values were obtained for all drug concentrations used. The method showed specificity and selectivity with linearity in the working range and good precision and accuracy, making it very suitable for quantitation of triamcinolone in PLGA microparticles.
Keywords: Analytical method validation; HPLC analytical method; PLGA microparticles; Triamcinolone; glycolic acid derivative; methanol; triamcinolone; water; biodegradability; concentration (parameters); diagnostic accuracy; diagnostic value; elution; flow rate; high performance liquid chromatography; injection; particle size; quantitative analysis; sample; standard; thermostability; validation study